Performative seduction: how management consultants influence practices of leadership. Issue 3 (23rd December 2020) - Ford, Jackie; Harding, Nancy
Abstract : Purpose: This paper tracks how a policy recommended by management consultants becomes embedded as an integral part of leadership practice. It explores the launch of the concept of "talent management" by McKinsey & Company and how it becomes adopted as part of expected leadership practices in the English National Health Service. The use of Management Consultants globally has increased exponentially, and the paper considers this phenomenon and the ways in which management consultant advice influences public sector leadership and practice at local level. Design/methodology/approach: A case study approach is adopted, focussing on the introduction of the concept of talent management into the English NHS, following the wider emergence of the concept through influential reports published by McKinsey & Company in the late 1990s. An analysis of the emergence of the concept is conducted drawing on this series of reports and the adoption of talent management policies and practices by the English government's Department of Health. Findings: These influential reports by the management consultancy firm, McKinsey & Company, constituted an urgent need for this newly identified concept of talent management and the secrecy surrounding its reception. It is this mystery surrounding the decisions about a talent management strategy in the NHS and the concealment of decisions behind closed doors, which leads us to offer a theory of management consultants' influence on leaders as one of performative seduction. Originality/value: Management consultancy is a vast business whose influence reaches deeply into public and private sector organisations around the world. Understanding of the variegated policies and practices that constitute contemporary modes of governance therefore requires comprehension of management consultants' role within those policies and practices. This paper argues that management consultants influence public sector leadership through insertion of their products into definitions of, and performative constitution of, local level leadership.